Characterization of Anopheles dirus glutathione transferase epsilon 4 - Gulsiri Charoensilp (2018)
The coding sequences of a wild type glutathione transferase (GST) Epsilon 4 and three isoenzymes were obtained by RT-PCR from a Thai malaria mosquito, Anopheles dirus. After confirmation by sequencing, the RT-PCR products were subcloned into an expression vector and proteins were expressed, purified, and biochemically characterized to study the function of these enzymes and for comparison with two orthologs from An. gambiae (agGSTE4-4) and Aedes aegypti (aaGSTE4-4). The results showed that An. dirus GST Epsilon 4 (adGSTE4-4) shares more than 85% amino acid sequence similarity with agGSTE4-4 and aaGSTE44. However, adGSTE4-4 possesses a greater catalytic efficiency (k cat/Km) for 1-chloro-2,4-dinitrobenzene as well as greater activities for several other substrates compared with agGSTE4-4 and aaGSTE4-4. Moreover, adGSTE4-4 enzyme possesses peroxidase and DDT dehydrochlorinase activities while these activities were not observed for agGSTE4-4. In addition, adGSTE4-4 binds two pyrethroid insecticides (permethrin and 1-cyhalothrin) with a relatively high affinity. We conclude that adGSTE4-4, unlike agGSTE4-4, can contribute to DDT resistance by DDT dehydrochlorinase activity as well as to pyrethroid resistance by sequestration and protection against oxidation from secondary pyrethroid metabolites via its peroxidase activity.